A general method to quantify ligand-driven oligomerization from fluorescence-based images - Stoneman, Michael R.; Biener, Gabriel; Ward, Richard J.; Pediani, John D.; Badu, Dammar; Eis, Annie; Popa, Ionel; Milligan, Graeme; Raicu, Valerică (Nature methods, 2019)
Here, we introduce fluorescence intensity fluctuation spectrometry for determining the identity, abundance and stability of protein oligomers. This approach was tested on monomers and oligomers of known sizes and was used to uncover the oligomeric states of the epidermal growth factor receptor and the secretin receptor in the presence and absence of their agonist ligands. This method is fast and is scalable for high-throughput screening of drugs targeting protein–protein interactions. Fluorescence intensity fluctuation spectrometry provides a rapid and accurate measurement of the identity, abundance and stability of protein oligomers.